1999
DOI: 10.1080/073993399245746
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Perceived Social Support, Self-Esteem, and Pregnancy Status Among Dominican Adolescents

Abstract: In this study I explore whether pregnancy status and mainland acculturation can be used to predict perceived social support or self-esteem in 49 nulligravida and 41 primigravida adolescents of Dominican background. Self-administered questionnaires containing the Dominican American version of the Acculturation Rating Scale (DARS), the Personal Resource Questionnaire-85 (PRQ85), the Rosenberg Self-Esteem Scale (RSES), and a pregnancy-specific demographic sheet were completed in the participant's choice of Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…The results contradicted prior assumptions that acculturation, in terms of host culture competence, should disrupt ethnic sources of social support (Contreras et al, 1999;Elder et al, 2000;Orshan, 1996Orshan, , 1999. The correlation between host competence and all sources of support was in the positive direction, if not always significant.…”
Section: Discussioncontrasting
confidence: 83%
“…The results contradicted prior assumptions that acculturation, in terms of host culture competence, should disrupt ethnic sources of social support (Contreras et al, 1999;Elder et al, 2000;Orshan, 1996Orshan, , 1999. The correlation between host competence and all sources of support was in the positive direction, if not always significant.…”
Section: Discussioncontrasting
confidence: 83%
“…Recently researchers reported coefficient alpha values ranging from .76 to .92 in samples of adolescents (Ayres, 2008;Cantrell, 2006;Mahat et al, 2002;Mahon et al, 2004;Yarcheske et al, 2001). This instrument has also been translated into Spanish and used with adolescents reporting alpha coefficients ranging from .84 to .89 (Orshan, 1999;Yarcheske et al, 1992). The alpha coefficient in this study for the PRQ85 was α = .87.…”
Section: The Personal Resource Quesionnaire-85 (Prq85)mentioning
confidence: 89%
“…Fleming and Courtner (1980) reported an internal consistency coefficient of .88 with for a similar sample. In studies with Dominican adolescents using the Spanish version of the scale, Orshan (1999) reported an alpha coefficient of .64 and Babington et al (2009) reported a coefficient of α = .71. The alpha coefficient for the RSES in this study was α = .87.…”
Section: Rosenberg Self-esteem Scalementioning
confidence: 96%
See 1 more Smart Citation
“…Fleming and Courney (1980) reported an internal consistency coefficient 0f .88 with for a similar sample. Orshan (1999), in a study with Dominican adolescents, reported an alpha coefficient of .64 for the Spanish version of the RSES. In the present study, the reliability estimate was a = .71.…”
Section: Rosenberg Self-esteem Scalementioning
confidence: 96%